A Metallocene Molecular Complex as Visible‐Light Absorber for High‐Voltage Organic–Inorganic Hybrid Photovoltaic Cells. Issue 6 (14th April 2014) - Ishii, Ayumi; Miyasaka, Tsutomu
Abstract A thin solid‐state dye‐sensitized photovoltaic cell is fabricated by composing organic and inorganic heterojunctions in which the visible‐light sensitizers are cyclopentadiene derivatives (Cp*) coordinated to a metal oxide, typically TiO2. The coordination bonds of the metallocene molecular complex (Ti–Cp*) create a new LMCT (ligand‐to‐metal charge transfer) absorption band and induce a rectified charge transfer from the organic ligands to TiO2, leading to photocurrent generation. Photovoltaic junctions are completed by coating crystalline organic molecules (perylene) as a hole‐transport layer on the Cp*‐coordinated TiO2 surface by using the vapor deposition method. The molecular plane of Cp* on the TiO2 surfaces seems to help the hole‐transport layer to form ordered structures, which effectively improve carrier conductivities and minimize interfacial resistance. The organic–inorganic hybrid thin‐film photocell with metallocene molecular complexes is capable of generating high open‐circuit voltages exceeding 1.2 V.